Exploring the Parameters of Fractional Domination Number in Litact Graph - Meenakshi. M; Pankajam. V (Utilitas Mathematica, 2025)
The aim of this article is to investigate the concept of the fractional domination number of the Litact graph by establishing the bounds and relationships between the fractional domination number and other parameters in Litact graphs. This leads to a significant enhancement in resource allocation. The bounds based on the definitions of the fractional domination number and other parameters are calculated.The relation between the fractional mixed domination number, fractional domination number, and independent domination number of Litact graphs are derived. The primary findings include the effects on the bounds of the fractional domination number and the fractional mixed domination number when vertices or edges are added or removed from the graph.